Churches – Cathedral of St. John, Savannah Ga - Scholars wishing to... (Wikimedia Commons, 2010)
Carte postale ancienne issue de Wikimedia Commons. Titre: Churches – Cathedral of St. John, Savannah Ga. Color postcard printed on linen textured paper with No border and divided back. French settlers first established the parish of Congrégation de Saint Jean-Baptiste shortly before the end of the 18th century and established a small church in a wooden building. The parish quickly grew and selected another site on Drayton and Perry Streets. A church constructed of brick and seating 1,000 people was dedicated in 1839. The Church of St. John the Baptist became a Cathedral in 1850 when the Diocese of Savannah was erected and a new building was planned on Abercorn Street. The Cathedral cornerstone was laid in 1873 and the Cathedral was dedicated in 1876. It was constructed of brick Cathedral in the French Gothic style. Bronze-colored iron columns supported triple rows of arches across the front entrance. The main altar and four side altars, crafted of white Italian marble, were designed by Baldwin & Price of Baltimore. Spires were added in 1896, and the building was stuccoed and whitewashed. A fire of 1898 destroyed much of the building, but restoration was begun immediately. Several further renovations have occurred since, the latest in 1998, completed in 2000 to commemorate the 150th anniversary of the diocese. The publisher of the postcard was E. C. Kropp, of Milwaukee, Wisconsin. They published chromolithographic cards and, later, linen cards with a fine grain, between 1907 through 1956.
Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; église; port